2016
DOI: 10.1111/pai.12653
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of allergic children – Where is the progress (for the practicing allergist)?

Abstract: For any kind of therapeutic intervention in allergic diseases such as environmental control, pharmacological, or immunomodulating treatment including educational programs, children are addressed separately from adults. Health authorities like the Food and Drug Administration in the United States of America or the European Medicine Agency in Europe request a specific 'Pediatric investigational plan' with studies addressing dose-response relationship, safety, and efficacy for infants, children, and adolescents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 147 publications
0
4
0
3
Order By: Relevance
“…First‐line treatment of AR is based on oral and/or intranasal antihistamines and intranasal corticosteroids . Recently, bilastine, a second‐generation oral antihistamine, has shown to be tolerable in children from 2 years of age .…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…First‐line treatment of AR is based on oral and/or intranasal antihistamines and intranasal corticosteroids . Recently, bilastine, a second‐generation oral antihistamine, has shown to be tolerable in children from 2 years of age .…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Some authors reported a decrease in asthma symptoms and AR after intranasal corticosteroid treatment of rhinitis and a recent meta-analysis confirmed the beneficial effect of intranasal steroids in AR ( 41 ). LTRAs are known to be useful for long-term management of asthma patients complicated by AR ( 42 ).…”
Section: Clinical and Treatment Evidencementioning
confidence: 97%
“…З а прогнозами Всесвітньої організації охорони здоров'я (ВООЗ), до 2050 року від різноманітних алергозів буде страждати більша частина населення планети, при цьому алергеном може виступати будь яка речовина, а ХХІ століття стане епохою алергії [2,10,11,28]. До алергічних захворювань належать бронхіальна астма (БА), алергічний риніт (АР), алергічний кон'юнктивіт (АК), атопічний дерматит (АД) і кропив'янка, медикаментозна і харчова алергія (ХА), алергія на укуси комах, анафілаксія, ангіоневротичний набряк [1,9,13,15,23].…”
Section: ом мочульськаunclassified
“…Читайте нас на сайте: http://med expert.com.ua АД в АР і БА [3,4,10,15,28]. На сьогодні АСІТ є єдиним патогенетично обґрунтованим методом лікування IgE залежних алергічних захворювань, її дія орієнтована не на симпто ми алергії, а на патогенез самого захворюван ня [1,23].…”
Section: ом мочульськаunclassified
See 1 more Smart Citation